Metastable high entropy alloys - Liu, Xiongjun; Banerjee, Rajarshi; Vitos, Levente; Wang, Yandong (Applied physics letters, 2022)
High entropy alloys (HEAs) are a new family of alloys usually made up of five or more metallic elements in approximately equal proportions to maximize the configurational entropy, also termed as the multi-principal-element alloys or complex concentrated alloys. The unique features of structure and property render HEAs exciting potential for structural and functional applications, particularly for those cases under extreme conditions, which spark intense research activities in this area, ranging from the fundamental issues, such as phase formation and stability, to the engineering-related problems, such as fabrication, processing, and usage performance. HEAs are the focus of intense research in the fields of materials science and condensed matter physics. Compositional metastability in HEAs leads to decomposition of the complex concentrated solid solution via thermally activated processes, which results in the development of local chemical ordering, the precipitation of second phases, and the formation of a complex multi-phase microstructure.